Superficial zone cellularity is deficient in mice lacking lubricin: a stereoscopic analysis - Karamchedu, Naga Padmini (Arthritis Res Ther, 2016)
BACKGROUND: Lubricin, a mucinous glycoprotein secreted by synoviocytes and chondrocytes plays an important role in reducing the coefficient of friction in mammalian joints. Elevated cartilage surface friction is thought to cause chondrocyte loss; however, its quantification and methodological approaches have not been reported. We adapted a stereological method and incorporated vital cell staining to assess cellular loss in superficial and upper intermediate zones in lubricin deficient mouse cartilage. METHODS: The femoral condyle cartilage of the intact knees from lubricin wild type (Prg4 (+/+)), heterozygote (Prg4 (+/-)), and knockout (Prg4 (-/-)) mice was imaged using fluorescein diacetate (FDA), propidium iodide (PI), and Hoechst staining, and confocal microscopy. Three dimensional reconstructions of confocal images to a depth of 14 μm were analyzed using Matlab to determine the volume fraction occupied by chondrocytes in cartilage of both medial and lateral femoral condyles. Living chondrocyte volume fraction was defined as FDA stained chondrocyte volume/total volume of superficial + upper intermediate zone. Living and dead (total) chondrocyte volume fraction was defined as FDA + PI stained chondrocyte volume/total volume of superficial + upper intermediate zone. MicroCT provided an orthogonal measure of cartilage thickness. Immunohistology for activated caspase-3 and TUNEL staining were performed to evaluate the presence of apoptotic chondrocytes in Prg4 mutant mice. RESULTS: Living chondrocyte volume fraction of the medial femoral condyle was significantly lower in Prg4 (-/-) mice compared to Prg4 (+/+) (p = 0.002) and Prg4 (+/-) (p = 0.002) littermates. There was no significant difference in medial condyle chondrocyte volume fraction between Prg4 (+/+) and Prg4 (+/-) mice (p = 0.82). No significant differences were observed for the chondrocyte volume fraction for the lateral condyle (p > 0.26). Cartilage thickness increased in the medial condyle for Prg4 (-/-) mice compared to Prg4 (+/+) (p = 0.02) and Prg4 (+/-) (p = 0.03) littermates, and the lateral condyle for Prg4 (-/-) mice compared to Prg4 (+/+) (p < 0.0001) and Prg4 (+/-) (p < 0.0001) littermates, indicating that a multi-dimensional increase in cartilage volume did not artifactually lower the chondrocyte volume fraction in the medial condyle. Significantly higher number of caspase-3 positive cells were observed in the superficial and upper intermediate zone cartilage of the medial femoral condyle of Prg4 (-/-) mice compared to Prg4 (+/+) (p = 0.01) and Prg4 (+/-) (p = 0.04) littermates, and the lateral femoral condyle of Prg4 (-/-) mice compared to Prg4 (+/+) (p = 0.02) and Prg4 (+/-) (p = 0.02) littermates. There were no significant differences in TUNEL staining among different Prg4 genotypes in both condyles (p > 0.05 for all comparisons). CONCLUSIONS: Increased Caspase-3 activation is observed in Prg4 deficient mice compared to Prg4 sufficient littermates. Absence of Prg4 induces loss of chondrocytes in the superficial and upper intermediate zone of mouse cartilage that is quantifiable by a novel image processing technique. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13075-016-0967-4) contains supplementary material, which is available to authorized users.